SALES OF LOCAL GOODS TO THE INTERNATIONAL MARKET - Lia Yulia; Nina Herlina; Purnama Sari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
One of the mainstay products of Tasikmalaya City is Kelom Geulis. Kelom Geulis is taken from the Dutch